Extraction Optimization of Phenolic Compounds from Rimpang Lempuyang Gajah (Z. Zerumbet): Green Solvent (NADES-UAE) (Ultrasound-Assisted Extraction) and MAE (Microwave Assisted Extraction) - Berghuis, Nila Tanyela; Nursanto, Eduardus Budi; Nanda, Elsa Vera; Maryana, Erma; Tjokrokusuma, Donowati; Kurniawati, Fitri (Science and Technology Indonesia, 2025)
The Lempuyang plant is one of the medicinal plants in Indonesia. One of the plants of the Lempuyang family that has not been widely researched is Lempuyang Gajah Zingiber zerumbet (L.). The commonly used method of extraction of phenolic compounds is maceration with organic solvents. The disadvantages are the amount of organic solvents that must be used and the long extraction time (days). An environmentally friendly solvent that has been successfully developed in the 21st century is eutectic or known as Natural deep eutectic solvent (NADES). In addition, NADES can also be used in conjunction with other extraction methods such as (UAE), and microwave aid (MAE). The results obtained were the synthesis of NADES with HBA (Choline Chloride) and HBD variations (Glucose, Lactic Acid, and Ethylene Glycol) with ratios of 1:1 and 1:2. In the maceration process, variations in time (2, 4, 6 hours) and variations in extraction methods (maceration, UAE and UAE-MAE) are carried out. The best TFC (Total Flavonoid Content) value data was obtained by NADES D (choline chloride: glycerol 1:2) of 697.24 mg QE/g extract through a combined ultrasonic and microwave method (UAE-MAE) while the best TPC (Total Phenolic Content) was NADES C (choline chloride: glycerol 1:1) of 2491.88 mg GA/g extract through a combined ultrasonic and microwave method (UAE-MAE). Meanwhile, the characterization of NADES synthesis to see the interaction of hydrogen bonds through FTIR analysis, and the content of phenolic compounds and flavonoids was carried out through HPLC-DAD.